Liver function predicts survival in patients undergoing extracorporeal membrane oxygenation following cardiovascular surgery. Issue 1 (December 2016) - Roth, Christian; Schrutka, Lore; Binder, Christina; Kriechbaumer, Lukas; Heinz, Gottfried; Lang, Irene; Maurer, Gerald; Koinig, Herbert; Steinlechner, Barbara; Niessner, Alexander; Distelmaier, Klaus; Goliasch, Georg
Abstract Background Extracorporeal membrane oxygenation (ECMO) represents a valuable and rapidly evolving therapeutic option in patients with severe heart or lung failure following cardiovascular surgery. However, despite significant advances in ECMO techniques and management, prognosis remains poor and accurate risk stratification challenging. We therefore evaluated the predictive value of liver function variables on all-cause mortality in patients undergoing venoarterial ECMO support after cardiovascular surgery. Methods We included into our single-center registry a total of 240 patients undergoing venoarterial ECMO therapy following cardiovascular surgery at a university-affiliated tertiary care center. Results The median follow-up was 37 months (interquartile range 19–67 months), and a total of 156 patients (65 %) died. Alkaline phosphatase and total bilirubin were the strongest predictors for 30-day mortality, with adjusted hazard ratios (HRs) per 1–standard deviation increase of 1.36 (95 % confidence interval [CI] 1.10–1.68;P  = 0.004) and 1.22 (95 % CI 1.07–1.40;P  = 0.004), respectively. The observed associations persisted for long-term mortality, with adjusted HRs of 1.27 (95 % CI 1.03–1.56;P  = 0.023) for alkaline phosphatase and 1.22 (95 % CI 1.07–1.39;P  = 0.003) for total bilirubin. Conclusions The present study demonstrates that elevated values of alkaline phosphatase and total bilirubin are sensitive parameters for predicting the short-term and long-term outcomes of ECMO patients.